2014
DOI: 10.1007/s12264-014-1470-z
|View full text |Cite
|
Sign up to set email alerts
|

Small-animal PET demonstrates brain metabolic change after using bevacizumab in a rat model of cerebral ischemic injury

Abstract: To evaluate the effect of bevacizumab on cerebral ischemia, we used 2-deoxy-2-18 F-fluoro-D-glucose ( 18 F-FDG) small-animal positron emission tomography (PET) in the middle cerebral artery occlusion (MCAO) rat model. After baseline neurologic function tests and PET studies, MCAO Sprague-Dawley rats received bevacizumab or normal saline (controls). Weekly PET imaging and neurologic function tests showed that the 18 F-FDG accumulation in the bevacizumab group was similar to that in the controls during the fi rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
9
2
Order By: Relevance
“…This model reproduces cerebral ischemia and reperfusion injuries that involve both the frontoparietal cortex and the lateral caudoputamen without craniotomy in mice and rats [9, 12, 3336] . In this model, a filament (mono-nylon suture, silicone/poly- L -lysine-coated suture, 4-0 for rats and 6-0 for mice) is inserted to the point of origin of the MCA through the internal carotid artery (ICA).…”
Section: Ischemic Stroke Modelsmentioning
confidence: 99%
“…This model reproduces cerebral ischemia and reperfusion injuries that involve both the frontoparietal cortex and the lateral caudoputamen without craniotomy in mice and rats [9, 12, 3336] . In this model, a filament (mono-nylon suture, silicone/poly- L -lysine-coated suture, 4-0 for rats and 6-0 for mice) is inserted to the point of origin of the MCA through the internal carotid artery (ICA).…”
Section: Ischemic Stroke Modelsmentioning
confidence: 99%
“… 36 , 37 PET with 18 F-FDG has been widely used in the evaluation of the effects of drugs for cerebrovascular disease via the quantitative and noninvasive monitoring of glucose metabolism. 12 , 38 , 39 In the current study, micro-PET imaging technology was used to further confirm the validity of YQFM treatment in I/R-treated mice. We found that YQFM improved brain glucose metabolism, which was consistent with the results of TTC staining ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 93%
“…Sildenafil has been found to protect against cerebral edema [ 15 , 16 ] and to serve as an appropriate therapy for patients with stroke [ 23 ]. Accordingly, in an experimental study of the poststroke effects of bevacizumab [ 24 ], researchers treated Sprague-Dawley rats with bevacizumab or saline following induction of MCAO and analyzed the findings with positron emission tomography in conjunction with behavioral analysis. Their results suggested that bevacizumab has no effect on functional recovery after stroke [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in an experimental study of the poststroke effects of bevacizumab [ 24 ], researchers treated Sprague-Dawley rats with bevacizumab or saline following induction of MCAO and analyzed the findings with positron emission tomography in conjunction with behavioral analysis. Their results suggested that bevacizumab has no effect on functional recovery after stroke [ 24 ]. However, positron emission tomography showed a decreased metabolic demand for glucose and inhibition of vascular formation, which could explain our finding of a neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%